Synthesis, Characterization and Chromogenic Properties of Lead (II) Complexes Containing Hydrazonic Ligands - Rassem, Hesham H. A.; Nour, A. H. (AENSI Publishing, 2015)
The hydrazine and hydrazide compounds were subjected to condensation reaction with ketone and different aldehyde derivatives affording the corresponding expected hydrazones.Tow hydrazone ligands, namely, 4-hydroxy-(2-hydroxy-3-methoxybenzylidene)benzohydrazide(L1) and 4-hydroxy-(2-hydroxy-4-methoxybenzylidene) benzohydrazide(L2) were synthesized and characterized. The complexationof these ligands with Pb2+ was also investigatedand characterized. The chemical structures were found to be consistent with both analytical and spectroscopic data (CHN, FTIR, UV/Vis, TGA, 1H NMR and 13C NMR). The stoichiomtric ratio of their complexes with Pb2+ was found to be 1:1 for (L1-Pb2+) and (L2-Pb2+). The chromogenic properties of the ligands upon their complexation with Pb2+ was carried out in different solvents including methanol, ethanol, acetone, acetonitrile, dimethylsulphoxide, and tetrahydrofuran. DMSO was found to be the best solvent forthe complexation.